2021
DOI: 10.1039/d1ra02510d
|View full text |Cite
|
Sign up to set email alerts
|

Typical antibiotics in the receiving rivers of direct-discharge sources of sewage across Shanghai: occurrence and source analysis

Abstract: In Shanghai, the antibiotics in the receiving rivers of direct-discharge sources of sewage (aquaculture farms, cattle farms and wastewater treatment plants) were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…It has been reported that animal-derived food plays a key role in human exposure to antibiotics via dietary intake. , Due to the decreasing tendency in antibiotic usage per ton of animal products in China since 2014, the rise in concentrations of antibiotics in the urine collected from the general population in the test areas in 2020 (compared to 2017) was likely due to increased intake of antibiotics (self-medication) during the COVID-19 pandemic, especially considering the relatively lower bioavailability of antibiotics through oral uptake than via intravenous injection . Moreover, consistent with the above-mentioned results, relatively higher levels of sulfadiazine, sulfamethoxazole, and sulfamethazine (divided into the sulfonamide group), as well as ofloxacin (divided into the fluoroquinolone group), were found in the receiving rivers of sewage across Shanghai in November 2020 (range: nd to 76.7, 8.83–35.1, 10.9–332, and nd to 40.0 ng/L) than those in November 2014 (nd to 53.9, nd to 26.0, nd to 10.1, and nd to 16.1 ng/L). , …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…It has been reported that animal-derived food plays a key role in human exposure to antibiotics via dietary intake. , Due to the decreasing tendency in antibiotic usage per ton of animal products in China since 2014, the rise in concentrations of antibiotics in the urine collected from the general population in the test areas in 2020 (compared to 2017) was likely due to increased intake of antibiotics (self-medication) during the COVID-19 pandemic, especially considering the relatively lower bioavailability of antibiotics through oral uptake than via intravenous injection . Moreover, consistent with the above-mentioned results, relatively higher levels of sulfadiazine, sulfamethoxazole, and sulfamethazine (divided into the sulfonamide group), as well as ofloxacin (divided into the fluoroquinolone group), were found in the receiving rivers of sewage across Shanghai in November 2020 (range: nd to 76.7, 8.83–35.1, 10.9–332, and nd to 40.0 ng/L) than those in November 2014 (nd to 53.9, nd to 26.0, nd to 10.1, and nd to 16.1 ng/L). , …”
Section: Resultssupporting
confidence: 71%
“… 6 Moreover, consistent with the above-mentioned results, relatively higher levels of sulfadiazine, sulfamethoxazole, and sulfamethazine (divided into the sulfonamide group), as well as ofloxacin (divided into the fluoroquinolone group), were found in the receiving rivers of sewage across Shanghai in November 2020 (range: nd to 76.7, 8.83–35.1, 10.9–332, and nd to 40.0 ng/L) than those in November 2014 (nd to 53.9, nd to 26.0, nd to 10.1, and nd to 16.1 ng/L). 60 , 61 …”
Section: Resultsmentioning
confidence: 99%
“…These antibiotic residues, which are excreted directly or indirectly from hospitals (waste and wastewater), animal breeding facilities, industrial facilities, aquaculture fields and human feces or urine reach wastewater treatment plants. (Kümmerer et al 2000;Li et al 2021). Since almost all general wastewater treatment plants in the world are designed on the basis of removing C, N, P and some other main pollutants, it has been proven by many studies that these existing wastewater treatment plants are not sufficient for the removal of antibiotics (Al-Gheethi et al 2015;Lien et al 2016;Russell and Yost 2021).…”
Section: Introductionmentioning
confidence: 99%